Hacia una pedagogía más cristiana - Manuel Ruiz Jurado (Jesuit University Ignatianum in Krakow, 2017)
Every pedagogical system assumes certain concept of man. Philosophy open to the light of Revelation allows to look at man from the angle of his destination, framed by God - the Creator and Saviour. In Jesus Christ God fully reveals man to man (Vaticanum II). Education should lead to the realization of Christ's image in the pupil. Therefore, we should aim for pedagogy more distinctly Christocentric. There will always be certain disparity between the suggested ideal and concrete reality. Nonetheless, working out a Christian pedagogical system, clear goals have to be deﬁ ned. Formation should develop the attitude of availability towards God, obedience to His will. This availability will constitute a measure of Christian maturity. We have to shape attitudes typical of the "new man" following the example of Christ, according to His proposal: "Whoever wishes to come after Me must deny himself, take up his cross, and follow Me" (Matthew 16,24). The condition for such a plan for life is the attitude of spiritual discernment: openness to the Holy Spirit activity and identifying the signs of God's presence and His plans in events, in needs and deep desires of contemporary people. Educational plan, focusing on Christ, does not mean religious integrism, which wants to impose itself with violence, but constitutes an offer of truth, to be accepted by man in a free and conscious way.